2009
DOI: 10.1089/mdr.2009.0872
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Action of Ebselen on Fluconazole-ResistantCandida albicans: Role of the Plasma Membrane H+-ATPase

Abstract: PMA1 is a yeast gene that codes for the plasma membrane H(+)-ATPase, a protein commonly referred to as Pma1p. Ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one) is a synthetic selenium-containing compound that has recently been shown to display antimicrobial activity owing to its ability to inhibit Pma1p. Ebselen is able to block the activity of Pma1p not only in opportunistic pathogens such as Cryptococcus neoformans and Candida albicans but also in nonpathogenic yeasts such as Saccharomyces cerevisiae. A seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…The PCL was selected as the compound library because it is compact (1,200 compounds) and also because published data which would aid interpretation of the results are available on each compound. Of the nine hits identified in the PCL screen, four (flupentixol, prochlorperazine, droperodol, and ethoxyquin) are known inhibitors or inducers of human ABC transporters (15,25,26,36), and four (ebselen, econazole, sulconazole, and disulfiram) have known antifungal activity (2,3,20,49,53). The finding that eight of nine hits detected in the screen, excepting clorgyline, had been shown previously to interact with efflux pumps and/or show antifungal activity validated our assay and this approach to screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCL was selected as the compound library because it is compact (1,200 compounds) and also because published data which would aid interpretation of the results are available on each compound. Of the nine hits identified in the PCL screen, four (flupentixol, prochlorperazine, droperodol, and ethoxyquin) are known inhibitors or inducers of human ABC transporters (15,25,26,36), and four (ebselen, econazole, sulconazole, and disulfiram) have known antifungal activity (2,3,20,49,53). The finding that eight of nine hits detected in the screen, excepting clorgyline, had been shown previously to interact with efflux pumps and/or show antifungal activity validated our assay and this approach to screening.…”
Section: Discussionmentioning
confidence: 99%
“…Clorgyline is a monoamine oxidase A (MAO-A)-selective inhibitor, which is no longer in use as an antidepressant because of dietary interactions, i.e., the "cheese effect" (4). Ebselen, a seleno-organic compound showing glutathione peroxidase-like activity, has previously reported antifungal activity (2,3) and is believed to act via inhibition of the fungal plasma membrane ATPase (3). However, only clorgyline inhibited R6G efflux from both strains by more than 93% at a concentration of 5 M, yet did not show antifungal activity at concentrations that inhibited efflux ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Bowman et al (1997) demonstrated that 64 of 66 mutations that rescued concanamycin A-mediated V-ATPase inhibition in N. crassa were localized to the PMA1 gene. The synthetic organoselenium compound ebselen is a known inhibitor of Pma1p (Chan et al, 2007; Billack et al, 2009). Ebselen exhibits anti-fungal activity against wild-type strains of C. albicans (Soteropoulos et al, 2000; Bouhafs and Jarstrand, 2002; Wojtowicz et al, 2004) as well as fluconazole-resistant strains (Billack et al, 2009).…”
Section: Current Utility Of V-atpase As An Anti-fungal Drug Targetmentioning
confidence: 99%
“…The synthetic organoselenium compound ebselen is a known inhibitor of Pma1p (Chan et al, 2007; Billack et al, 2009). Ebselen exhibits anti-fungal activity against wild-type strains of C. albicans (Soteropoulos et al, 2000; Bouhafs and Jarstrand, 2002; Wojtowicz et al, 2004) as well as fluconazole-resistant strains (Billack et al, 2009). These results again demonstrate the precedence that targeting components of the V-ATPase pathway, even via a downstream element such as Pma1p, can circumvent the drug resistance that has developed against presently available therapies.…”
Section: Current Utility Of V-atpase As An Anti-fungal Drug Targetmentioning
confidence: 99%
“…It displays synergistic effect with azoles against azoleresistant strains of both C. albicans and C. glabrata in vitro. On the other hand, ebselen is known to have antifungal activity by inhibition of Pma1, the main plasma membrane H + -ATPase (Billack et al 2009). Other potent ABC pump inhibitors are the milbemycins (antiparasitic agents of macrolide type) , unnarmicins (bacterial cyclic peptides) ), tetrandrine (anti-inflammatory calcium channel blocker) (Zhang et al 2009), enniatins (cyclic depsipeptides) (Hiraga et al 2005), and ofloxacin and grepafloxacin (both synthetic fluoroquinolone antibiotics) (Sasaki et al 2000).…”
Section: Drug Combinations and Perspectivesmentioning
confidence: 99%